Here's the question you clicked on:
Yahoo!
1+2+4+8+16+32.............. = ? Find the Sum
1 (1+2+4+8+16+32.............. ) (2-1)(1+2+4+8+16+32.............. ) = 2 + 4 +8+ 16 +32 ....... -1-2-4-8-16-32.......... = -1
Lol...i knw....Nw tell me wats the wrong in my sloution
huh they haven't given the last term and btw its basically a geometric progression
Do u Find any mistake in the way i did....
yeah !!!!! there is a mistake in ur where did that -1 come from????
2-1 = 1...................lol
... 4, 8, 16, 32 ... 512 or 4(1), 4(2), 4(4), 4(8), ... , 4(128) or 4(2^0), 4(2^1), 4(2^2), 4(2^3), ... , 4(2^7) S(n) = 4 ∑ 2^k [ k = 0 to n ] ....... = 4 [ 2^(n+1) - 1 ] S(7) = 4 [ 2^(7+1) - 1 ] ....... = 1020
Lol....i dont need the answer..) i want to knw is there any mistake in my solution
don't angry @Yahoo! it's my limit
lol....i am not angry ...this is a Funny....question....
just apply my method and get the answer
@Yahoo! : its not that let the series be A by ur terms => (2-1)A =>2A -A =A
oho...Again..... Tell me is there any wrong...lol
\[\Huge{\bf{\color{blue}{i know you can }\color{red}{doit}}}\]
I hate these! I can't see see what is wrong but obviously there is something as it should total infinity... I would just do the 2-1 in the bracket and get the same answer... (is it not that there will always be one last term in the positive set of numbers which is much bigger than its negative counterpart in that set, and eventually that is infinity..?)
1 (1+2+4+8+16+32.............. ) (2-1)(1+2+4+8+16+32.............. ) = 2 + 4 +8+ 16 +32 ....... -1-2-4-8-16-32.......... = -1
Also... first terms, 2-1 = 1, second terms: 4-2 = 2, so you DO get the original series back, and it does NOT equal -1.
2+4+8+16+32..................+2n 1+2+4+8+16+32............. + n {subtracting} ----------------------------- 1+2+4+8+16 +32+...........n
take make sense @DHASHNI
exactly @DHASHNI ! have a medal too :)
You are subtracting sets of different cardinality. That's like adding unlike terms, you can't do it.
1 (1+2+4+8+16+32.............. ) (2-1)(1+2+4+8+16+32.............. ) = (2 + 4 +8+ 16 +32 +64+......)+( -1-2-4-8-16 -32 .........) = 63+.....